A new resorcinol derivative from the bark of Aegiceras floridum (Primulaceae). Issue 13 (1st July 2022) - Luu, Huynh-Van-Long; Nguyen, Thi-Hoai-Thu; Nguyen, Kim-Phi-Phung; Nguyen, Huu-Hung; Nguyen, Ngoc-Hong; Duong, Thuc-Huy
Abstract: Chemical investigation of the Vietnamese plant Aegiceras floridum Roem. & Schult. (Primulaceae) led to the isolation of the new compound 3-methoxy-5-nonylphenol (1 ) along with five known ones 2, 8, 10-trihydroxy-6 H -benzo[ c ]chromen-6-one (2 ), 2-hydroxy-5-methoxy-3-nonylbenzo-1, 4-quinone (3 ), 5-(3-hydroxypropyl)-7-methoxy-3-(methylbenzofuran-2-yl)-3-methoxyphenol (4 ), 2, 8-dihydroxy-7-methoxy-3, 9-diundecyldibenzofuran-1, 4-dione (5 ) and 10-hydroxy-4-methoxy-2, 11-diundecylgomphilactone (6 ). The structures were elucidated by analysis of their HRESIMS and NMR data as well as the comparison of their NMR data with those reported in the literature. The cytotoxic activity of selected isolated compounds against some cancer cell lines such as human epithelial carcinoma (HeLa), human lung cancer (NCI-H460), liver hepatocellular carcinoma (HepG2), human breast cancer (MCF-7), and acute T cell leukemia (Jurkat) was evaluated. Among them, 3 showed moderate activities against MCF-7 with an IC50 of 17.77 µM and NCI-H460 with an IC50 of 25.02 µM. The result of DPPH radical scavenging activity assay indicated that compounds 2–4 and 6 revealed weak antioxidant activity. Graphical Abstract: UF0001